COVID-19: What Consequences for Higher Education in Africa? - Mohamedbhai, Goolam (International Higher Education, 2020)
COVID-19 will have serious consequences for the higher education sector in Africa. It will give rise to inequities resulting from the use of ICT, affect the quality of teaching and learning, jeopardize research funding, exacerbate graduate unemployment, and place private institutions at risk. Urgent action is needed at the level of each country for readiness when the crisis is over, otherwise recovery of the sector may be too slow, too late.